Impact of SARS-Cov-2 Virus and The Pandemic on Tinnitus Patients: A Comparative Cross-sectional Study: Impact of SARS-Cov-2 Virus on Tinnitus - Awais, Amna; Awan, Nukhbat Ullah; Saqulain, Ghulam; Azmat, Shahana; Zaman, Sher; Laraib, Paras; Shahzad, Shafqat (Pakistan Journal of Health Sciences, 2023)
The WHO declared Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2) a "Public Health Emergency" before the end of January 2020. Over 6M people have died out of 593 million recorded cases. Objective: To determine the effect of the COVID-19 and the pandemic on tinnitus patients. Methods: Comparative Cross-sectional study was conducted at Mayo Hospital, Lahore. Total 110 patients with tinnitus were included in this study using convenience sampling. Sample included both genders, aged 17 and above with Group A including patients who were inflicted from SARS-COV-2 and group B who did not encounter the virus. Tinnitus Severity Index and a questionnaire was used for data collection. A relationship between the tinnitus severity scale scores obtained before suffering from the coronavirus and after suffering from it. Similarly, a relationship between tinnitus severity scale scores obtained before the occurrence of pandemic and after it, was determined in COVID-19 negative group. T-test, Chi-square and ANOVA statistics were utilized to determine difference between groups with p<0.05 considered significant. Results: Tinnitus was significantly (p=0.000) more bothersome during pandemic compared to before COVID-19 became pandemic, however having COVID-19 infection or not before (p=0.067) and during (p=0.234) pandemic did not reveal significant difference. TSI scores were higher in patients who picked COVID-19 infection compared to living in pandemic though not significant (p=0.375), however there was differences in characteristics of tinnitus. Conclusions: COVID-19 pandemic has produced a significant impact on tinnitus patients with more impact resulting from COVID-19 infection compared to pandemic itself, however this was not significant.